2003
DOI: 10.1016/s1525-0016(02)00058-8
|View full text |Cite
|
Sign up to set email alerts
|

Zinc enhancement of nonviral salivary gland transfection

Abstract: Gene transfer to exocrine glands, including the major salivary glands, presents an attractive method to deliver proteins for therapeutic applications. Previous efforts using nonviral gene delivery to these glands have resulted in limited success. In this report, zinc and other divalent transitions were coadministered with plasmid DNA in an effort to improve nonviral salivary gland transfection efficiency. The inclusion of zinc into plasmid DNA solutions resulted in a 20-fold enhancement in transgene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The zinc concentrations (1.8 or 3.6 mM) used in this and subsequent studies were those that were previously found to be optimal for SG transfection. 6 Administration of plasmid DNA without added zinc or ATA did not result in plasma SEAP concentrations above the SEAP assay background (50 pg/ml). For all the formulations screened, transgene expression in either plasma or tissue samples was transient, with a maximum observed at 48 h post-DNA administration (data not shown).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The zinc concentrations (1.8 or 3.6 mM) used in this and subsequent studies were those that were previously found to be optimal for SG transfection. 6 Administration of plasmid DNA without added zinc or ATA did not result in plasma SEAP concentrations above the SEAP assay background (50 pg/ml). For all the formulations screened, transgene expression in either plasma or tissue samples was transient, with a maximum observed at 48 h post-DNA administration (data not shown).…”
Section: Resultsmentioning
confidence: 88%
“…6 It was hypothesized that this increased transfection activity may be attributed to zinc-mediated inhibition of DNase activity. ATA, another known DNase inhibitor, was evaluated in this context.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations